2008
DOI: 10.1002/jccs.200800132
|View full text |Cite
|
Sign up to set email alerts
|

Silica Sulfuric Acid and Al(HSO4)3: As Efficient Catalysts for the Formylation of Alcohols by Using Ethyl Formate under Heterogeneous Conditions

Abstract: A mixture of ethyl formate and a catalytic amount of silica sulfuric acid or Al(HSO4)3 as suitable formylating systems can formylate various alcohols to their corresponding formate ester derivatives under mild, nearly neutral and heterogeneous conditions at room temperature with good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…In continuation of our studies on the host-guest chemistry of crown ethers, [36][37][38] the synthesis and application of tribromide reagents 24,39 and the protection of organic functional groups, [40][41][42][43][44] we found that addition of Br 2 to cryptand 222 in ethanol as solvent gave the unique tribromide reagent [H 2 -cryptand 222](Br 3 ) 2 (I) which was isolated as red crystals following recrystallization from acetonitrile, (Scheme I).…”
Section: Resultsmentioning
confidence: 92%
“…In continuation of our studies on the host-guest chemistry of crown ethers, [36][37][38] the synthesis and application of tribromide reagents 24,39 and the protection of organic functional groups, [40][41][42][43][44] we found that addition of Br 2 to cryptand 222 in ethanol as solvent gave the unique tribromide reagent [H 2 -cryptand 222](Br 3 ) 2 (I) which was isolated as red crystals following recrystallization from acetonitrile, (Scheme I).…”
Section: Resultsmentioning
confidence: 92%
“…Phenols were also, acetylated in short reaction times with acetic anhydride in the presence of SBNPSA (Table 3, entries [14][15][16][17]. It is important to note that according to the previous report 39 most of these acylation reactions proceeded at 62-80°C in the presence of sulfamic acid.…”
Section: Acetylationmentioning
confidence: 99%
“…Also, formamides employed as the major protecting groups of amines in peptide synthesis because the deprotection process can selectively take place in the presence of acetate or other ester protective groups . There are different methods for the protection of amines and alcohols in the form of formylation in the presence of various catalysts such as TiO 2 ‐P 25 , γ‐Fe 2 O 3 @HAp‐SO 3 H, HCOONa, CO 2 and Ph 2 SiH 2 , CO 2 /PhSiH 3 /TBAF, Silica sulfuric acid, HClO 4 –SiO 2 , Al (HSO 4 ) 3 and Silphos [PCl 3 ‐nSiO 2 ) n ] …”
Section: Introductionmentioning
confidence: 99%